An Analysis of News Sentiment, Exchange Rate, and Interest Rate on Indonesia's Expected and Realized Economic Growth Indicators - Fritzco Fernando; Amrita Nugraheni Saraswaty (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In recent years, both global and domestic economic uncertainties have increasingly influenced the movement of Indonesia’s JCI and GDP. This study aims to examine how various factors including news sentiment, exchange rates, and interest rates affect the JCI as a proxy for economic growth expectations, and GDP as a reflection of actual economic growth. Using quarterly data from 2016 to 2024, the analysis is conducted through the Auto Regressive Distributed Lag (ARDL) model to identify both short-term and long-term effects. The results show that these variables collectively have a significant impact on both the JCI and GDP. In the short term, the JCI is found to respond more quickly to changes in information and policy, reinforcing its role as a leading indicator. In contrast, GDP responds more slowly, with exchange rates and the BI interest rate showing a significant influence in the long term. These findings highlight that economic information and policies may affect the financial market and the real economy differently, underscoring the importance of understanding expectation dynamics in assessing the direction of Indonesia’s economic growth.